Environmental migration and human rights: Clues for the debate - Alarcão, V.; Candeias, P.; Stefanovska-Petkovska, M. (Environmental health behavior: Concepts, determinants, and impacts, 2024)
Migration represents a global phenomenon already having serious impacts on the lives of millions of people across the world. It is estimated that by 2050, it will result in 25 million to 1 billion more environmental migrants in the world. The purpose of this chapter is to contribute to the discussion of some of the climate change-induced migration ethical-related issues through the human rights lens. Drawing together from the relevant literature in this field, the chapter provides a fresh perspective on the nexus of environmental migration and human rights. Four key themes are explored: the first part provides a theoretical reflection on the nexus between the environment and migration. The second part defines the particularities and possible classifications of environmental migrations and sets out some of the difficulties encountered in the analytical separation and quantification of the phenomenon of environmental migration. The third segment discusses the potential link between climate change, migration, and environmental sustainability and the final, the fourth segment, explores the intersections of environmental justice. The text provides an excellent contribution to the emerging literature on environmental migration and will be of use to scholars in the fields of climate change, migration and refugee studies, and human rights law.